Simulação da variabilidade climática em diferentes cenários na disponibilidade hídrica nas bacias do córrego Queima Pé e do rio Ararão no Mato Grosso - Redivo, Polyana Comino (2020)
Anthropogenic intensification and global climate change pose challenges to the planning and management of water resources to ensure sustainable development. The watersheds of Queima Pé (BCQP) and River Ararão (BRA) in Mato Grosso-Brazil, it has been showing problems of scarcity and water stress over the years. In view of this, we sought to simulate climatic variability in different scenarios in water availability (Q95) in such watersheds, For this, the federal water availability database, precipitation, evapotranspiration and average air temperature obtained by MCG CCSM4 and scenarios RCP4.5 and RCP8.5 were used, and the connexion of these variables with the topography of the watersheds by Worldclim , in addition to the simplified water balance to obtain the streamflow As a current result, mini watersheds have been identified with critical concern. Nevertheless, for the different estimated future scenarios, the variability on the behavior of precipitation and evapotranspiration was noted, with an increase for the average temperature over the years. The future scenarios of the Q95 reference flows indicated for the annual scale the decrease over the years for the entire spatialization of the watersheds, specifically in 29 and 33% for the Queima Pé and 11 and 20% for the Ararão, inferring incipient behavior streamflow in the longer periods. For the seasonal scale, the reduction of Q95 was also illustrated during the dry season with an amortization of the rainy season for the longest periods. RCP8.5 demonstrated greater changes in all studied variables.